An Incomplete Transition : Overcoming the Legacy of Exclusion in South Africa - World Bank (Washington, DC: World Bank, 2022)
South Africa has come a long way since the advent of democracy, but its transition remains incomplete. Poverty has declined significantly since 1994, but inequality remains extremely high. Improved access to basic services (such as electricity, water, and sanitation), the provision of over 4 million houses through state programs, and the expansion of the social wage have considerably improved living standards for millions of South Africans. Creating jobs, especially for young people, is critical to overcome the legacy of exclusion. Jobs are also important to build a stronger social contract. This SCD identifies five key constraints. These are (i) insufficient skills; (ii) the skewed distribution of land and productive assets, and weak property rights; (iii) low competition and low integration in global and regional value chains; (iv) limited or expensive spatial connectivity and under-serviced historically disadvantaged settlements; and (v) climate shocks: the transition to a low-carbon economy and water insecurity.